Public Relations Campaign Strategy "Ready for Safe Tourism" of PT TWC (PERSERO) - Deo Pietra Nirwana; Riski Damastuti (Jurnal Spektrum Komunikasi, 2022)
The COVID-19 pandemic has affected various business lines' financial and operational conditions, especially the tourism business. Entering the New Normal, PT Taman Wisata Candi Borobudur, Prambanan, and Ratu Boko (Persero) seek to revive tourism through the "Ready For Safe Tourism" campaign. This research is a qualitative descriptive study that aims to determine the Public Relations campaign strategy "Ready For Safe Tourism" carried out by PT TWC (Persero). The research data was taken by interview and observation techniques. The interviewees were the Corporate Communications team of PT TWC, which were selected through purposive technique. Observations were made by observing PT TWC's social media and mass media coverage of the "Ready For Safe Tourism" campaign activities. The results of this study indicate that PT TWC performs fact-finding, planning, communicating, and evaluation stages in designing and implementing the "Ready For Safe Tourism" campaign strategy. In this campaign, PT TWC collaborates with several stakeholders to hold special events and social media optimization to convey campaign messages. This campaign activity cannot be carried out regularly due to the dynamic development of Covid-19.